On Eigendecomposition-based algorithms as feature extraction techniques used with hidden Markov model for the detection of whale vocalisations - Usman, Ayinde Mohammed (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.